A proteção processual da posse nos conflitos coletivos interétnicos - Holliday, Pedro Alberto Pereira de Mello Calmon (2016)
Ethnic conflicts between european white man and indigenous peoples through possession of the land, are present in all continents on earth, from the Inuits of the circumpolar region the Maoris of New Zealand, through the island Papuans in Indonesia and coming to the American Indians . Although perennial and universal, its causes, consequences and solutions are still little explored by the social sciences and the legal anthropology. Understanding this secular struggle for land occupation is the guide line of this research, adopting as an investigative method the historical survey, philosophical, sociological and legal right of possession and ownership, since its legitimacy by right of conquest and just war, until his resignation in current democratic constitutional regimes. A first approach reveals Portuguese Crown legislation never dreamed of attributing possessory rights to Indians, or refund the domain of their lands, serving only as a political game of deception and domination. The indigenato theory developed by João Mendes Junior (1912), assuring the a congenital native right, did not host the positive law. The Federal Constitution of 1988, while recognizing the Indians the right to a social organization, an ethnic identity and a habitat, linked the usufructuary possession of the land the objective facts, subordinate to traditional occupation and permanent housing, prior to 10.05.1988. Interpretations influenced by anthropological concepts without the legaldogmatic rigor, have to admit the revival of extinct indigenous communities claiming land with consolidated occupation by non-Indians. These ethnogenesis resulted in an immediate systemic invasions process (retake) of farms, many of them expropriated before the legal demarcation procedures. This aggression to the possession and property without observance of constitutional precepts, including due process of law, has transferred to judiciary branch the solution to this structural injuctions of wide proportions, encouraging the multiplication of guardianships possessory intertidal. Considered the social, political, ideological and legal reasons that surround this collective dispute, we can deduce that the appropriate management of procedural civil law are able to guarantee fundamental rights. The final scope of work is to demonstrate that the procedural science has mediation mechanisms that peasant tension, is to ensure the Indian people them ownership of their traditional territories recognized by the State, or repel unfair aggression to the heritage of non-Indians.